2005
DOI: 10.1253/circj.69.55
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Off Value of the Ankle-Brachial Pressure Index at Which the Accuracy of Brachial-Ankle Pulse Wave Velocity Measurement is Diminished

Abstract: ulse wave velocity (PWV) is used in the management of atherosclerotic cardiovascular disease as a validated marker of disease severity and a predictor of future events. [1][2][3][4] Recently, the use of brachial -ankle PWV, which can be obtained by simply wrapping the 4 extremities with blood pressure cuffs, was validated 5-7 and the technique is quite simple it is thus useful for screening the general population; in addition, the ankle -brachial blood pressure index (ABI) can also be simultaneously obtained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 19 publications
0
69
2
Order By: Relevance
“…In particular, care should be taken in the interpretation of baP-WV among subjects with reduced ABI. In such subjects, baPWV is decreased and does not accurately reflect central arterial stiffness 12,26) . In conclusion, this study provides further information showing that baPWV correlated best with aortic PWV among the five PWV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, care should be taken in the interpretation of baP-WV among subjects with reduced ABI. In such subjects, baPWV is decreased and does not accurately reflect central arterial stiffness 12,26) . In conclusion, this study provides further information showing that baPWV correlated best with aortic PWV among the five PWV measurements.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the reliability of the brachial-ankle PWV measurement is diminished in subjects with atrial fibrillation, frequent arrhythmias, or inaccurate pulse wave recordings because of arterial stenosis (e.g., ankle brachial pressure index 0.95) 8,13,14) .…”
Section: Standardizationmentioning
confidence: 99%
“…The brachial-ankle pulse wave velocity (baPWV) was measured bilaterally using a volume-plethysmographic apparatus PWV/ABI device (Colin Medical Technology Company, Komaki, Japan) in accordance with a methodology described elsewhere (5), and the mean value was calculated as a parameter of arteriosclerosis. Values are expressed as the mean±SEM.…”
Section: Arteriosclerosismentioning
confidence: 99%